Mapping the Serological Prevalence Rate of West Nile fever in Equids, Tunisia. Issue 1 (21st March 2013) - Bargaoui, R.; Lecollinet, S.; Lancelot, R.
Summary West Nile fever (WNF) is a viral disease of wild birds transmitted by mosquitoes. Humans and equids can also be affected and suffer from meningoencephalitis. In Tunisia, two outbreaks of WNF occurred in humans in 1997 and 2003; sporadic cases were reported on several other years. Small‐scale serological surveys revealed the presence of antibodies against WN virus (WNV) in equid sera. However, clinical cases were never reported in equids, although their population is abundant in Tunisia. This study was achieved to characterize the nationwide serological status of WNV in Tunisian equids. In total, 1189 sera were collected in 2009 during a cross‐sectional survey. Sera were tested for IgG antibodies, using ELISA and microneutralization tests. The estimated overall seroprevalence rate was 28%, 95% confidence interval [22; 34]. The highest rates were observed (i) in the north‐eastern governorates (Jendouba, 74%), (ii) on the eastern coast (Monastir, 64%) and (iii) in the lowlands of Chott El Jerid and Chott el Gharsa (Kebili, 58%; Tozeur, 52%). Environmental risk factors were assessed, including various indicators of wetlands, wild avifauna, night temperature and chlorophyllous activity (normalized difference vegetation index: NDVI). Multimodel inference showed that lower distance to ornithological sites and wetlands, lower night‐time temperature, and higher NDVI in late spring and late fall were associated with higher serological prevalence rate. The model‐predicted nationwide map of WNF seroprevalence rate in Tunisian equids highlighted different areas with high seroprevalence probability. These findings are discussed in the perspective of implementing a better WNF surveillance system in Tunisia. This system might rely on (i) a longitudinal survey of sentinel birds in high‐risk areas and time periods for WNV transmission, (ii) investigations of bird die‐offs and (iii) syndromic surveillance of equine meningoencephalitis.